The relationship of anxiety levels before and during the match with the performance of pencak silat athletes - Firman Nur Hakim Kusmaeli; Muhammad Saleh; Firman Maulana (Universitas Sriwijaya, 2025)
Background of the Problem: Anxiety is one of the psychological factors that athletes often experience, both before and during the game. Anxiety levels can affect focus, self-control, and decision-making in competition. Research Objectives: This study aims to determine the relationship between anxiety levels before and during matches and the performance of pencak silat athletes at Tapak Suci Cikidang Club. Methods: This study uses a quantitative approach with a correlational method. The sample amounted to 25 athletes who participated in the Mini Event 2 championship and were selected using the purposive sampling technique. The research instruments included pre-match anxiety questionnaires, post-match anxiety, and athletes' performance measured using a Likert scale of 1-4. Results: The results of the Pearson correlation test showed that there was no significant relationship between pre-competition anxiety and athlete performance (r = -0.182; p = 0.384 > 0.05), and anxiety during competition with athlete performance (r = -0.075; p = 0.721 > 0.05). The multiple linear regression test showed a simultaneous significant value of p = 0.638 (> 0.05), which means that there was no significant effect of the two forms of anxiety on athletes' performance simultaneously. Conclusion: These findings indicate that anxiety, both before and during the match, was not the dominant factor influencing the performance of pencak silat athletes in the context of this study. The results suggest that coaches place more emphasis on confidence development, relaxation techniques, and simulation of competing conditions to support athletes' optimal performance, as well as a reference for future research to reach a wider population and consider other variables.